2014
DOI: 10.1097/ico.0000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ranibizumab and Bevacizumab on Corneal Neovascularization in Rabbits

Abstract: Subconjunctival administrations of ranibizumab or bevacizumab inhibit corneal NV in rabbits and have equivalent effects on it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…29,31 Researchers even compared the therapeutic effect between bevacizumab and ranibizumab in animal models and had diverse findings from different settings. Some studies demonstrated no difference between the two agents with subconjunctival injection, 21 whereas others showed relatively less NV, 23,25,26 shorter blood vessels, 23,25 lower corneal opacity score, 25 and lower degree of inflammation 26 in the groups treated with bevacizumab compared to those treated with ranibizumab. However, a small, prospective, openlabeled, nonrandomized clinical study showed that ranibizumab was superior to bevacizumab in the onset of action and degree of efficacy when administrated by the topical route.…”
Section: Anti-vegf-a Antibodiesmentioning
confidence: 98%
See 1 more Smart Citation
“…29,31 Researchers even compared the therapeutic effect between bevacizumab and ranibizumab in animal models and had diverse findings from different settings. Some studies demonstrated no difference between the two agents with subconjunctival injection, 21 whereas others showed relatively less NV, 23,25,26 shorter blood vessels, 23,25 lower corneal opacity score, 25 and lower degree of inflammation 26 in the groups treated with bevacizumab compared to those treated with ranibizumab. However, a small, prospective, openlabeled, nonrandomized clinical study showed that ranibizumab was superior to bevacizumab in the onset of action and degree of efficacy when administrated by the topical route.…”
Section: Anti-vegf-a Antibodiesmentioning
confidence: 98%
“…22 With persistent topical administration, the therapeutic effect could even last longer than infrequent early-phase subconjunctival injections in a silver/ potassium nitrate cauterized model. 21 However, when the topical or subconjunctival administration of bevacizumab was postponed 2 weeks after suture injury in an animal model, its effect of reducing corneal NV was not so significant. 27 Ranibizumab is a fab fragment of antibody against VEGF-A.…”
Section: Anti-vegf-a Antibodiesmentioning
confidence: 98%
“…The comparison of anti‐CNV effect between bevacizumab and ranibizumab is controversial. Further researches are needed to resolve the contradiction …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 99%
“…71 No significant differences have been reported comparing the efficacy and safety profile between bevacizumab and ranibizumab for both topical and subconjunctival administration. 30,85 Although topical ranibizumab and bevacizumab both effectively reduced corneal neovascular area, vessel caliber and invasion area in two prospective studies on human eyes, ranibizumab may be favourable in reducing CoNV and have an effect earlier in the course of treatment than bevacizumab due its smaller molecular size and better penetration through the corneal epithelium. 30,86 Subconjunctival injections of ranibizumab and bevacizumab have been shown to result in significantly less CoNV in rat models compared with placebo, with no significant difference between these two anti-VEGF agents.…”
Section: Vegf Inhibitorsmentioning
confidence: 99%
“…30,86 Subconjunctival injections of ranibizumab and bevacizumab have been shown to result in significantly less CoNV in rat models compared with placebo, with no significant difference between these two anti-VEGF agents. 85 Most clinical studies suggest that the topical or subconjunctival use of bevacizumab and ranibizumab is a relatively safe and welltolerated option for the treatment of CoNV with no reported serious side effects. [70][71][87][88] Intrastromal injections of anti-VEGF might be an efficient and safe alternative 89 and may be considered particularly for intrastromal neovascularisation and in the presence of lipid keratopathy.…”
Section: Vegf Inhibitorsmentioning
confidence: 99%